Efectos de la globalización en las migraciones internacionales - Muñoz-Jumilla, Alma Rosa (Papeles de Población, 2021)
The purpose of this article is to demonstrate how economic globalization is a factor that has encouraged and has accelerated international migratory movements in the last decades. The extensive bibliography related to both current themes, has made it possible to analyze how these processes (economic globalization and international migration) are related. We begin this article by defining economic globalization and by acknowledging the difficulty of defining such a multidimensional term. Moreover, a historic analysis will show that “globalization” experiences in the past had also affected the international migratory patterns. It is our objective to compare and contrast the past experiences with this current wave of economic globalization. The extent of this work has also made it possible to analyze the migration flow from its origin to its destiny. We will define it as “the new geography of migrations”.